Rua da Frente: Avenida Getúlio Vargas como contexto na prostituição em São Carlos - SP - Rodrigues, André Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work concerns the occupation, appropriation and transformation of an urban public space by prostitution in the city of São Carlos, in the São Paulo state. It thus joins the discussion on urban spaces and the dynamics of medium-sized cities from the perspective of Urban Anthropology. The aim is to determine why, how and when Getúlio Vargas Avenue became a place of prostitution. In addition to that, I observed how São Carlos residents, especially those living near the space in question, relate to it and to the activities conducted therein. Finally, I observed the appropriation of the space by prostitutes and how this occurred. To this end, I conducted an ethnographic study in the area during the nighttime, another during daytime and I also studied it's an ethnography of a narrative. In terms of methodology, the area was approached as a context, as proposed by Roy Wagner (2012), with a focus on the relationships established within the urban space, as well as on the contacts that this space provides. Following urbanistic transformations and conflicts among the prostitutes, they went on to occupy the place and refer to it as Street. I treated the word Street as an analytical category, establishing a dialogue with the categories House, Street, Turf, Patch, Route, Circuit, and Code-Territory, showing its potential for the expansion of the reflection on the appropriation of the urban space by the subjects

Este trabalho é sobre as transformações, ocupações e apropriações do espaço público urbano por prostituição na cidade de São Carlos, interior do Estado de São Paulo. Inserindo-se, assim, na discussão sobre espaço urbano e a dinâmica das cidades médias na perspectiva da Antropologia Urbana. Objetivei saber a razão, desde quando e como é que a Avenida Getúlio Vargas havia se tornado lugar de prostituição. Juntamente com isso, observei como os são-carlenses, sobretudo dos bairros próximo à região, se relacionavam com o espaço e com a atividade ali desenvolvida. E por fim, observei as apropriações do espaço pelas prostitutas e como o produziam. Para tanto, realizei uma etnografia sobre a região no período noturno, uma no período diurno e uma etnografia sobre uma narrativa. Metodologicamente a região foi entendida como um contexto no sentido aplicado por Roy Wagner (2012), visando as relações que se instauram no espaço urbano e os contatos que este propicia. Após transformações urbanísticas e conflitos entre as prostitutas, as mesmas ocuparam o lugar classificando-o como Rua. Trabalhei a expressão Rua como categoria analítica, travando diálogo com as categorias Casa, Rua, Pedaço, Mancha, Trajeto, Circuito e Código-Território; mostrando sua potencialidade para expansão da reflexão sobre apropriação do espaço urbano pelos sujeitos
Keywords: Prostituição; Prostitutas; Antropologia; Anthropology; São Carlos (SP)